Progressive sarcopenia and myosteatosis predict prognosis of advanced HCC patients treated with immune checkpoint inhibitors - Liu, Mengchen; Jin, Qianna; Wang, Huiyan; Li, Yunqiao (Frontiers in Immunology, 2024)
Background: Immunotherapy stands as a pivotal modality in the therapeutic landscape for the treatment of advanced hepatocellular carcinoma, yet responses vary among patients. This study delves into the potential impact of sarcopenia, myosteatosis and adiposity indicators, as well as their changes during immunotherapy, on treatment response and prognosis in patients with advanced hepatocellular carcinoma treated with immune checkpoint inhibitors. Methods: In this retrospective analysis,116 patients with advanced hepatocellular carcinoma receiving immune checkpoint inhibitors were recruited. Skeletal muscle, intramuscular, subcutaneous, and visceral adipose tissue were assessed by computed tomography at the level of the third lumbar vertebrae before and after 3 months of treatment. Sarcopenia and myosteatosis were evaluated by skeletal muscle index and mean muscle density using predefined threshold values. Patients were stratified based on specific baseline values or median values, along with alterations observed during the treatment course. Overall survival （OS）and progression-free survival （PFS）were compared using the log-rank test and a multifactorial Cox proportional risk model. Results: A total of 116 patients were recruited and divided into two cohorts,81patients for the training set and 35 patients for the validating set. In the overall cohort, progressive sarcopenia （P=0.021） and progressive myosteatosis （P=0.001） were associated with objective response rates, whereas progressive myosteatosis （P<0.001） was associated with disease control rates. In the training set, baseline sarcopenia, myosteatosis, and subcutaneous and visceral adipose tissue were not significantly associated with PFS and OS. In multivariate analysis adjusting for sex, age, and other factors, progressive sarcopenia（P=0.002） and myosteatosis （P=0.018） remained independent predictors of PFS. Progressive sarcopenia （P=0.005）， performance status （P=0.006） and visceral adipose tissue index （P=0.001） were all independent predictors of OS. The predictive models developed in the training set also had good feasibility in the validating set. Conclusions: Progressive sarcopenia and myosteatosis are predictors of poor clinical outcomes in patients with advanced hepatocellular carcinoma receiving immune checkpoint inhibitors, and high baseline visceral adiposity is associated with a poorer survival.